The surgeon and the shepherd : two resistance heroes in Vichy France - Ostrum, Meg (University of Nebraska Press, 2004)
"Of the thousands of people who escaped through the Pyrenees during World War II, at least one hundred owe their lives to a daring scheme that Belgian Charles Schepens masterminded in Mendive, a remote Basque village near the French-Spanish border. The story of this near-miraculous resistance effort, an epic undertaking carried out in full view of the Nazis, is recounted in full for the first time in The Surgeon and the Shepherd, a tale of wartime heroism as incredible as it is true."